Fulfilment of Women Prisoners’ Rights (Case Study of Class II B Penitentiary in North Maluku) - Sri Mardiana Joisangadji; Faissal Malik; Suwarti Suwarti (Journal of Social Science, 2023)
This study aims to analyze the fulfillment of the special rights of female convicts in the Class II B Penitentiary of North Maluku Province and examine the obstacles and efforts faced by the North Maluku Class II B penitentiary in the process of fostering female convicts. The research method used in this study is a type of empirical legal research. Empirical legal research is to study the legal situation or facts obtained in people's lives. This type of research is often referred to as Socio Legal Research. In empirical legal research, what is initially studied is secondary data which is then followed by research on primary data in the field. The fulfillment of the special rights of female prisoners in the Class II B Penitentiary of North Maluku Province is explicitly regulated in Article 14 paragraph (1) jo Article 9 of Law Number 22 of 2022 concerning Correctional Services, it is expressly stated that the convict has the right such as to worship in accordance with his religion or beliefs, receive both spiritual and physical care, receive education and teaching, get health services and eat properly, and filing a complaint.